2014
DOI: 10.1038/onc.2014.102
|View full text |Cite|
|
Sign up to set email alerts
|

MUC4 regulates cellular senescence in head and neck squamous cell carcinoma through p16/Rb pathway

Abstract: The limited effectiveness of therapy for patients with advanced stage Head and Neck Squamous Cell Carcinoma (HNSCC) or recurrent disease is a reflection of an incomplete understanding of the molecular basis of HNSCC pathogenesis. MUC4, a high molecular weight glycoprotein, is differentially overexpressed in many human cancers and implicated in cancer progression and resistance to several chemotherapies. However its clinical relevance and the molecular mechanisms through which it mediates HNSCC progression are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 54 publications
(73 reference statements)
1
30
0
Order By: Relevance
“…P16 is involved in premature senescence as a tumor suppressor, 32 which is also involved in replicative senescence by the P16-RB pathway. 33 Thus, we explored the role of β -Arrestin1 on telomere-related replicative senescence, and found that β -Arrestin1 regulated the senescence via the hTERT -telomerase-telomere axis. However, the clear role of P16 gene on this process still need further study.…”
Section: Discussionmentioning
confidence: 99%
“…P16 is involved in premature senescence as a tumor suppressor, 32 which is also involved in replicative senescence by the P16-RB pathway. 33 Thus, we explored the role of β -Arrestin1 on telomere-related replicative senescence, and found that β -Arrestin1 regulated the senescence via the hTERT -telomerase-telomere axis. However, the clear role of P16 gene on this process still need further study.…”
Section: Discussionmentioning
confidence: 99%
“…induction of p16 mRNA by microRNA (miR-877-3p) as shown in bladder carcinoma [19] ; as well as MUC4-modulated cellular senescence pathways, which have found to be p16dependent in HNSCC [20] . Furthermore, Nindl et al described higher frequency of mutations in CDKN2A in metastatic cSCCs as compared to primary tumours [8,15] .…”
Section: Discussionmentioning
confidence: 98%
“…Finally, a gene set enrichment analysis showed that the high expression YRNA1 group was not enriched in any gene set, however, the low expression YRNA1 group was highly enriched in protein secretion processes, epidermal growth factor receptor binding, the RB-dependent pathway, the EIF4E-dependent pathway, the ERBB2-dependent pathway, the VEGF-dependent pathway, the EGFR-dependent pathway, and the cAMP-dependent pathway. These pathways are highly correlated with processes that occur during cancer development, such as enhanced proliferation, differentiation, and angiogenesis [22][23][24][25][26]. Moreover, the enhanced EIF4E-dependent pathway, which is responsible for translation initiation, was previously indicated to be overexpressed in the FaDu cell line, which is known to be the most aggressive HNSCC cell line [17].…”
Section: Discussionmentioning
confidence: 98%